Information elements of culture (un)favorable to the implementation of the new organizational structure of the sistem of libraries from UFPB (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
This research aims to analyze the implications of the information culture of the Library System of the Federal University of Paraíba, as a facilitator for the implementation of the new organizational structure. Methodologically, the research is descriptive, with a qualitative approach. Regarding the means, it is characterized as documentary and field research. A questionnaire with open and closed questions, analysis of documents, a semi-structured interview and direct observation that allowed the using of the approach strategy of triangulation data were adopted as research instrument. To analyze the data, we employed the method of content analysis. The results indicate that the information culture, active in the Library System, does not contribute to the implementation of the new organizational structure taking into account that the demonstration of informational intricacies does not have equities in information behavior between strategic management and tactics adopted in the system. The results suggest that managers of sectorial libraries and system need to face the challenge of building together in a systematic, structured and participatory culture informational possible to concatenate in its structure the formal and informal means of communication. Keywords: Informational Culture. Organizational Culture. Information Behavior. Information Science. Academic Library.Link para o texto completo (PDF)http://www2.marilia.unesp.br/revistas/index.php/bjis/article/view/3128/2470